SOCIO-PSYCHOLOGOICAL CHARACTERISTICS OF INTERPERSONAL RELATIONSHIPS IN PRESCHOOL CHILDREN (American Journal of Research in Humanities and Social Sciences, 2024)
Interpersonal relationships play a crucial role in the socio-emotional development of preschool children. This article explores the socio-psychological characteristics that shape interpersonal relationships among preschoolers, including attachment, empathy, prosocial behavior, peer acceptance, and conflict resolution skills. It examines how these characteristics influence the quality of relationships and social interactions within the preschool setting. The article highlights the importance of fostering positive socio-psychological development and provides recommendations for supporting healthy interpersonal relationships among preschool children. By understanding and addressing these characteristics, educators and parents can create a nurturing environment that promotes social-emotional well-being and positive relationship building in preschoolers.